Innovative Game-Based Learning in Islamic Education for Quality Education (SDG-4) - Muhamad Rizza; Agus Nurdiana; Hilma Fatimatul Zahro; Ahmad Fawaiz Hakim; Muhammad Firdaus; Badrudin Badrudin (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
Although Game-Based Learning (GBL) has considerable potential to support quality education, research on its implementation in Islamic primary education remains limited. This study aims to analyze the relationship between GBL and students’ understanding of Fiqh, particularly the topic of fasting (Sawm), in relation to the achievement of SDG 4. Using a quantitative design, the study involved 65 students selected through purposive sampling. Data were collected through questionnaires and comprehension tests and analyzed using descriptive statistics, Pearson correlation, and regression analysis. The findings reveal a strong positive relationship between student engagement and comprehension (r = 0.825, p < 0.001), indicating that higher engagement significantly improves learning outcomes and supports constructivist learning theory. The study concludes that GBL plays an important role in enhancing both the cognitive and affective dimensions of learning in Islamic education. These findings contribute theoretically to the development of digital pedagogy in Islamic education and offer practical implications for educators seeking to adopt interactive learning strategies that support SDG 4. The study also highlights opportunities for future research involving broader Islamic subjects, diverse educational contexts, and mixed-method approaches.